Common agricultural weeds among alien invasive plants in China: Species lists and their practical managing strategies - Zeyue Huang; Min Lin; Guoqi Chen (Heliyon)
Plant invasion is a big challenge to weed management of agricultural lands. In order to reveal the list of common weed species among alien invasive plants, and reveal practical management strategies, we extracted the species lists of common alien agricultural weeds (CAAWs) of various arable lands and plantations, by comparing the lists of alien invasive plant species and common weed species published in China. Totally 88 species from 18 families were recognized as CAAWs, among which 43.0 % are native to North America, followed by South America (34.4 %), Europe (29.0 %), Asia (23.7 %) and Africa (17.2 %); 62.4 % were introduced into China from 1840 to 1949. CAAWs such as Aegilops tauschii Coss., Alopecurus myosuroides Huds., Lolium multiflorum Lamk, Avena fatua L., Phalaris minor Retz, Phalaris paradoxa L., Veronica persica Poir., Geranium carolinianum L., Ranunculus muricatus L., and Cerastium glomeratum Thuill. frequently infest highlands with summer-ripe crops such as wheat and oilseed rape; Alternanthera spp., Panicum repens L., Paspalum conjugatum Bergius, and Ageratum conyzoides L. frequently infest highlands with autumn-ripe crops; and Paspalum distichum L., Alternanthera philoxeroides, and Ammannia coccinea Rott. occasionally infest rice fields. Troublesome CAAWs in plantations in China mainly consist of tall herbs, and climbing or spiny plants, such as Mikania micrantha Kunth, Ipomoea spp., Solidago canadensis L., Erigeron spp. and Bidens spp. Management strategies against CAAWs in current China mainly rely on chemical control, tillage, soil mulching, and manual removing of weeds. Next, effective risk assessing models targeting to different sorts of arable lands or plantations are urgently needed; as well, effective, feasible and sustainable integrated management strategies against troublesome CAAWs should be developed and applied.